Relationship Satisfaction Pada Mahasiswa Yang Berpacaran Ditinjau Dari Perilaku Phubbing - Farida Novitasari; Yuarini Wahyu Pertiwi; Tiara Anggita Perdini (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2021)
Relationship satisfaction is an interpersonal evaluation and the main assessment in a relationship by involving thoughts and feelings, where in this study the feeling in question is satisfaction. Individuals who feel relationship satisfaction will have better mental and physical health and have the readiness to change bad behavior for the better. Relationship satisfaction can be influenced by the quality of communication. As technology develops and the COVID-19 pandemic changes the quality of communication changes, giving rise to phubbing behavior. The purpose of this study was to determine whether phubbing behavior was able to predict relationship satisfaction in dating students at Bhayangkara University, Jakarta Raya. The research method used is quantitative-causality with convenience sampling technique. The results showed that phubbing behavior was able to predict relationship satisfaction significantly because p = 0.000 or p <0.05. Based on these results, it can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected, which means that phubbing behavior is able to predict relationship satisfaction in students who are dating at Bhayangkara University, Jakarta Raya. The next research is expected to be able to examine other factors and increase the literature so that the research becomes better.